Procalcitonin Level at 24 Hours of Age May be Predictive for Transient Tachypnea of the Newborn - Tarakcı, Nuriye; Altunhan, Hüseyin; Sarı, Eyüp; Uyar, Mehmet (Journal of Pediatric Infectious Diseases, 2020)
Objective It is an important problem to differentiate transient tachypnea of the newborn (TTN) from bacterial pneumonia or other conditions in patients admitted to Neonatal Intensive Care Unit. The aim of this study was to evaluate the predictive value of procalcitonin (PCT) for TTN.Methods A total of 52 infants were contained in the study. The patients were divided into three groups. Group 1 consisted of patients with pronounced grunting at more than 2 hours postnatal age (n = 16). Group 2 consisted of patients whose grunt was reduced or gone at 2 hours postnatal age but in whom tachypnea persisted until 24 hours postnatal age (n = 18). Group 3 consisted of patients with minimal or no respiratory distress at 24 hours postnatal age (n = 18). In all groups, PCT concentrations were determined at birth and 24 hours postnatal age.Results PCT concentrations at birth were significantly higher in Group 1 than other groups, but there was no difference between Groups 2 and 3. PCT concentrations at 24 hours postnatal age were significantly higher in Groups 1 and 2 than Group 3. No difference was found between Group 1 and Group 2 at 24 hours postnatal age. All PCT concentrations in Group 3 were significantly lower than other groups. PCT thresholds for the diagnosis of TTN were 0.44 ng/mL at birth (sensitivity 58%, specificity 50%) and 5.11 ng/mL at 24 hours postnatal age (sensitivity 79.4%, specificity 89.1%).Conclusion Serial PCT measurements at birth and postnatal 24 hours may be helpful in differentiating between pneumonia and TTN. Further researches are needed to confirm this initial study.
Keywords: procalcitonin; transient tachypnea of the newborn; neonatal sepsis